Cultivation of an edible mushroom species, Pleurotus sajor – caju (Fr.) Singer (1951) (Pleurotaceae) (strain 221114) on various lignocellulosic substrates. - Roger Batubenga; Félicien Lukoki; Esther Mwambay; Daddy Kanika; Alain Tshisuaka; Jeff Iteku; Jean Paul Koto-Te-Nyiwa Ngbolua; Simon Dibaluka (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The current food crisis and the continuing deterioration in the health of the populations of the DRC in general, and those of the province of Kongo Central in particular, are among the causes of severe pressure on natural environments, especially forests. In the long term, these risks creating scarcity or the disappearance of certain resources, including mushrooms. The main aim of this study is to contribute to the promotion of NTFPs in the fight against hunger and food insecurity through the cultivation of strain 221114 of the species Pleurotus sajor-caju, making sporophores available on a regular basis. To achieve this objective, we set ourselves the specific goals of determining the mycelial growth rate and comparing the yields obtained from strain 221114 of the species Pleurotus sajor-caju on fruiting substrates. The strain used in the culture was isolated in the Ngeba area, as shown in Figure 1 below, in the province of Central Kongo. The preparation of seedling media and the production of seedling whites, the preparation of final substrates, the addition of nutrients, incubation, fruit induction, and obtaining and harvesting sporophores were carried out at the Systematic Mycology and Myciculture Laboratory of the Life Sciences Department, Faculty of Science and Technology, University of Kinshasa, in room B28 and the department's experimental garden. The fungal material used was strain 221114 of Pleurotus sajor – caju. The plant material for the substrate consisted of rice straw, banana leaves, wood chips, sugarcane bagasse, and sawdust. Wheat bran and slaked lime were used as additives. The isolation method from tissue or tissue culture (known as monoculture) was used to start the culture. The best average sporophore yields were 35.01 ± 3.7% on rice straw, 28.67 ± 4% on wood chips, and 23.3 ± 2.4% on sugarcane bagasse, yields well above the theoretical yield of 20% at which a substrate is considered best and suitable for sporophore production.